Investigation of the structural performance of two flexible pipes set in one trench with a new placement method for separate sewer systems. (October 2019) - Abbas, Alaa; Ruddock, Felicite; Alkhaddar, Rafid; Rothwell, Glynn; Carnacina, Iacopo; Andoh, Robert
Graphical abstract: Highlights: An innovative method to install a separate sewer systems. Addressing the challenges associated with constructing a separate sewer system in narrow streets. Providing additional space for other infrastructure services. The structural performance of using one trench to accommodate two separate pipes in a one-over-one configuration. 3D FE models were utilized to test the behaviours of pipes in the proposed configuration methods. Abstract: Substantial research has been conducted on single flexible pipes buried in a trench. In contrast, the objective of this study is to determine the structural performance of two buried flexible sewer pipes positioned one over the other in a single trench. An innovative configuration is designed, based around the use of an innovative manhole structure which can accommodate both foul and surface water, to solve the challenges associated with constructing separate sewer systems in narrow streets while providing additional space for other infrastructure services. The behaviours of the two flexible pipes were tested using a 3D finite element (FE) model validated with experimental data from a laboratory investigation. A modified Drucker–Prager cap soil constitutive model was used to simulate the elasto-plastic soil behaviour. The results show that this approach comprising the use of a large-diameter flexible pipe set above a small-diameter flexible pipe mitigates the strain on the smaller pipe and decreases the total deflections of both pipes and the soil.